Discovery of a loose star cluster in the Large Magellanic Cloud - Piatti, Andres Eduardo (2016)
We present results for an up-to-date uncatalogued star cluster projected towards the Eastern side of the Large Magellanic Cloud (LMC) outer disc. The new object was discovered from a search of loose star cluster in the Magellanic Clouds' (MCs) outskirts using kernel density estimators onWashington CT1 deep images. Contrarily to what would be commonly expected, the star cluster resulted to be a young object (log(t yr-1) = 8.45) with a slightly subsolar metal content (Z = 0.013) and a total mass of 650M⊙. Its core, half-mass and tidal radii also are within the frequent values of LMC star clusters. However, the new star cluster is placed at the Small Magellanic Cloud distance and at 11.3 kpc from the LMC centre. We speculate with the possibility that it was born in the inner body of the LMC and soon after expelled into the intergalactic space during the recent MilkyWay/MCs interaction. Nevertheless, radial velocity and chemical abundance measurements are needed to further understand its origin, as well as extensive search for loose star clusters in order to constrain the effectiveness of star cluster scattering during galaxy interactions.